Novel Anti-Trop2 Nanobodies Disrupt Receptor Dimerization and Inhibit Tumor Cell Growth - Junwen Deng; Zhongmin Geng; Linli Luan; Dingwen Jiang; Jian Lu; Hanzhong Zhang; Bingguan Chen; Xinlin Liu; Dongming Xing (MDPI AG, 2024)
Background: Trop2 (trophoblast cell-surface antigen 2) is overexpressed in multiple malignancies and is closely associated with poor prognosis, thus positioning it as a promising target for pan-cancer therapies. Despite the approval of Trop2-targeted antibody-drug conjugates (ADCs), challenges such as side effects, drug resistance, and limited efficacy persist. Recent studies have shown that the dimeric forms of Trop2 are crucial for its oncogenic functions, and the binding epitopes of existing Trop2-targeted drugs lie distant from the dimerization interface, potentially limiting their antitumor efficacy. Method: A well-established synthetic nanobody library was screened against Trop2-ECD. The identified nanobodies were extensively characterized, including their binding specificity and affinity, as well as their bioactivities in antigen-antibody endocytosis, cell proliferation, and the inhibition of Trop2 dimer assembly. Finally, ELISA based epitope analysis and AlphaFold 3 were employed to elucidate the binding modes of the nanobodies. Results: We identified two nanobodies, N14 and N152, which demonstrated high affinity and specificity for Trop2. Cell-based assays confirmed that N14 and N152 can facilitate receptor internalization and inhibit growth in Trop2-positive tumor cells. Epitope analysis uncovered that N14 and N152 are capable of binding with all three subdomains of Trop2-ECD and effectively disrupt Trop2 dimerization. Predictive modeling suggests that N14 and N152 likely target the epitopes at the interface of Trop2 cis-dimerization. The binding modality and mechanism of action demonstrated by N14 and N152 are unique among Trop2-targeted antibodies. Conclusions: we identified two novel nanobodies, N14 and N152, that specifically bind to Trop2. Importantly, these nanobodies exhibit significant anti-tumor efficacy and distinctive binding patterns, underscoring their potential as innovative Trop2-targeted therapeutics.